The Unifying Language: Traces of Tolerance and Social Harmony in Palopo City - Kartini Kartini; Bungawati Bungawati; Wahibah Wahibah; Ulfiyah Ulfiyah; Zainur Roziqin (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Language plays a crucial role in building public awareness of the importance of tolerance, particularly amidst increasing cultural diversity and the potential for social friction in multicultural societies. Palopo City, a region with diverse ethnicities, languages, and social backgrounds, faces challenges in maintaining social harmony. This study aims to analyze the role of language in fostering tolerance and social harmony in the multicultural society of Palopo City. This study uses a qualitative approach with a field study method. Data collection techniques through observation, interviews, and documentation. The object of the study is the practice of language use in social interactions among residents of Palopo City. Data validity was tested using data triangulation and source triangulation. Data analysis includes three stages: data reduction, data presentation, and drawing conclusions. The results show that language functions as a communication tool, a unifying instrument, a means of strengthening relationships, and a form of social empathy. The practices of code switching, code mixing, and language adjustment according to the social context strengthen interethnic solidarity and prevent misunderstandings. These findings confirm that adaptive, polite, and contextual language practices contribute to the creation of a tolerant and harmonious society in Palopo City. The community, educators, and community leaders in Palopo City need to implement adaptive, polite, and inclusive language practices as a primary strategy in strengthening tolerance and social harmony in a multicultural society.